PENGOLAHAN MINYAK KEMIRI DENGAN CARA PELARUTAN DAN PENGEMPAAN - Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1995)
The objective of this research is to study the processing of candle nut oils by using solvent extraction and pressing techniques. In a solvent extraction technique, several solvents were applied in the experiment. The choice solvent was used to extract the treated candle nut seeds. In a pressing technique, five levels of pressing temperature were applied to extract untreated candle nut seeds. The effect of the temperatures was calculated by a complete randomized design. Relationship between the pressing temperature and oil properties was analysed with a polynomial orthogonal method.Results showed that a hexane solvent with pure analytical grade was the best solvent to extract candle nut oils as indicated by the highest yield of oils. Using this solvent, a dry-frying treatment on candle nut seeds gave the highest yield of oils, compared boiling and control treatments. In a pressing technique, the increasing of pressing temperature gave a highly significant effect on yields, specific gravity, peroxide and iodine numbers. It also gave a significant effecr on saponifiable number. A polynomial orthogonal analysis showed that pressing temperatures had a highly significant quadratic relationship to oil yields or iodine number, a linear relationship to peroxide number or spesific gravity, and a significant cubic relationship to saponification number. Based on the regression equation for iodine number, the optimum value of iodine number was obtained at a 93° C pressing temperature. At this temperature, the oil yield which could be produced was 59, 79 %. The candle ma oil produced at this temperature was the best oil quality, as indicated by the highest value of iodine number, 97.28.